2001
DOI: 10.1016/s0165-5876(00)00434-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and follow-up of children with hearing loss in Mauritius

Abstract: Early identification of hearing loss followed by a timely and effective intervention programme for children with hearing impairment is necessary to minimise the negative effects of hearing loss on the development of cognition, psychosocial and verbal communication skills. Such early intervention programmes need to be multidisciplinary, technologically sound and take cognisance of the context in which the child and family function. The main aim of this study is to obtain accurate and reliable baseline informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…[37] In 1999, Mukhari et al reported that hearing aids were fitted with an average of 5.32 years and In Mauritius, the median age of fitting hearing of hearing aid was found to be 30 months. [30][32] In yet another study the average delay between diagnosis and hearing and fitting was 3 months. [34] In the article of Sjoblad et al, the interval was reported to be 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…[37] In 1999, Mukhari et al reported that hearing aids were fitted with an average of 5.32 years and In Mauritius, the median age of fitting hearing of hearing aid was found to be 30 months. [30][32] In yet another study the average delay between diagnosis and hearing and fitting was 3 months. [34] In the article of Sjoblad et al, the interval was reported to be 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…47 The importance of community services that helped in improving communication and service delivery across different sectors was also stressed. 84 Three comprehensive reviews, 68,85,86 completed over a span of 10 years, provided similar recommendations such as increasing intersectoral collaboration, involvement of national and international agencies, developing community-based services, and increasing training of staff as some of the steps for improving disability-related services.…”
Section: Multiple Developing Countriesmentioning
confidence: 99%
“…Gopal et al 84 Identification of hearing impairment by specialists was within acceptable limits, but there was a need to improve the communication network between specialists and organizations involved in distribution of hearing aids; the role of community workers to improve the network was highlighted Nigeria and Uganda…”
Section: Epidemiologymentioning
confidence: 99%
“…In a study on 37 children from Mauritania with hearing downfall greater than 70 dB, the greatest delay in intervention related to the age of suspicion and recourse for evaluation (Gopal et al 2001). The mean age of suspicion of hearing loss was 12 months, with a mean age of hearing evaluation of 22 months (Gopal et al 2001).…”
mentioning
confidence: 99%
“…The mean age of suspicion of hearing loss was 12 months, with a mean age of hearing evaluation of 22 months (Gopal et al 2001).…”
mentioning
confidence: 99%